PENGARUH LATIHAN SHUTTLE RUN TERHADAP KELINCAHAN ATLET BULUTANGKIS PUTRA PB KKNP DUMAI - Haditya Primahari; Aref Vai; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The problem in this study is the agility of the men's badminton players PB KKNP Dumai that is not optimal points for opponents, the aim of this study was to determine the effect of shuttle run training on the agility of men's badminton athletes at PB KKNP Dumai. The population in this study consisted of all male badminton players using a total sample technique of 17 athletes. This type of study uses a single-group pre-test-post-test design, using the Hexagonal Obstacle Test. Based on the descriptive analysis of the pre-test data, there is a difference in the numbers increasing or increasing by 2.03. And based on statistical analysis, using the t-test yields a tcount of 9,666 and a ttable of 1,764. Means tcount > ttable Based on the above findings and data processing, the following can be concluded: There is an influence between shuttle run training (X) on agility (Y) in the male athletes of PB KKNP Dumai.Keywords: Shuttle Run, Agility, Badminton Training